"A grand sisterhood": Black American women speakers at the 1893 World's Congress of Representative Women. Issue 1 (2nd January 2021) - VanderHaagen, Sara C.
ABSTRACT: In May 1893, the World's Congress of Representative Women ("WCRW") convened alongside the Chicago World's Fair to commemorate the progress of women since 1492. The speeches of six Black women were recorded in the congress proceedings: Hallie Q. Brown, Anna J. Cooper, Fanny J. Coppin, Sarah J.W. Early, Frances E. W. Harper, and Fannie B. Williams. Invited to report on Black women's progress for a primarily white audience, these women nonetheless used their speeches to advance their own goals by arguing that a proper understanding of Black women's progress requires accurate memories of emancipation and enslavement, as well as a recognition of Black women's agency. They developed these arguments using three rhetorical moves: first, they reframed the commemorative situation by establishing emancipation rather than Columbus's landing as the "zero point"; second, they claimed that Black women's progress in the present could only be understood in relation to accurate accounts of enslavement; third, they centered Black women as the agents of their own progress in the past, present, and future. Reading these speeches together reveals the resonance between nineteenth-century women and twentieth- and twenty-first century Black feminist thought, and it illuminates Black American critiques of white history.